The role of Mg dopant concentration in tuning the performance of the SnO2 electron transport layer in perovskite solar cells - Sannino, Gennaro Vincenzo (2024)
Recent experiments pointed out a beneficial role of moderate Mg doping in SnO2 for application as an electron transport layer (ETL) in perovskite solar cells. The high efficiencies obtained with Mg-doped SnO2 are driven by an improved open circuit potential (VOC), but the origin of this behaviour is still under debate. Some ascribe this enhancement to the improved quality of the thin ETL film, while others speculate it is due to an electronic structure rearrangement upon Mg doping. In this context, here we applied density functional theory calculations to uncover the changes in SnO2 structural, electronic, and defect properties induced by different percentages of Mg doping. Our predictions of conduction band minimum (CBM) variations provide new insights on the trend of different VOC values observed in experiments. We found that low Mg contents push up the SnO2 CBM increasing the VOC. In contrast, at high dopant concentration, interstitial Mg defects are more likely to occur, leading to lower VOC and to the formation of intra-gap band states, explaining the decrease of PSC performances at a high Mg doping ratio. These findings provide a new atomistic perspective on the positive/negative effects of Mg dopants for the application of SnO2 in last-generation solar cells, highlighting key structural and defect properties that can be easily tuned to obtain ETL materials with purposely tailored electronic features.